Governance for private green spaces in a growing Indian city - Kulbhushan Balooni; Kausik Gangopadhyay and B. Mohan Kumar (Landscape and Urban Planning, 2014)
Urban green spaces are relatively scarce in developing countries, and such countries face challenges related to urban sustainability in view of rapid urbanization in the post-economicliberalization era. Although private green spaces constitute the core of urban sustainability, they have received far less attention compared to urban green spaces under the public domain. We studied the change in the home- gardens (a form of private green space with multistoried vegetation that abounds in the tropical regions) in the city of Kozhikode, Kerala, India. We assessed the dynamics of homegardens from 2000 to 2010 based on household socio-economic characteristics. The study reveals a decline of 11.5% in the cultivated plants in homegardens, reflecting the loss of urban sustainability. The floristic structure of small land- holdings has tilted toward food items—an indication of contribution of homegardens in complementing livelihood sustainability. After examining existing and possible policy mechanisms, we propose local community participation under the auspices of decentralized governance, which has now evolved as a major policy tool to achieve environmental sustainability in developing countries, for promotion and conservation of private green spaces.